The political sublime: from the starry sky to the law in the heart (stopping at the king’s scaffold) - Vázquez-Romero, José Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
According to Kant’s conception, the execution of the monarch means the reversal and the collapse of Law to the point of regarding such act as legal appearance. However, the real or virtual apprehension of the execution scene shakes the mind of the viewer in such a way, that its trains his imagination beyond its limits, to accommodate the undetermined influx of reason, which alone can rationalise that atrocious spectacle of symbolic chaos. Only through that sublime feeling, in which imagination flies off the handle, is it possible to transmute that terrible scene, making ussusceptible to the moral feeling, for which moral law echoes in the privacy of our consciousness, and which predisposes us to take sides with the revolution as a sign of progress of humankind.
Keywords: Kant; law; imagination; sublime; moral disposition; revolution.